Public contributors' preferences for the organization of remote public involvement meetings in health and social care: A discrete choice experiment study. (6th November 2022) - Loria‐Rebolledo, Luis E.; Watson, Verity; Hassan, Shaima; Gabbay, Mark; Tahir, Naheed; Hossain, Muhammad; Goodall, Mark; Frith, Lucy
Abstract: Introduction: Covid‐19 expanded the use of remote working to engage with public contributors in health and social care research. These changes have the potential to limit the ability to participate in patient and public involvement and engagement (PPIE) for some public contributors. It is therefore important to understand public contributors' preferences, so that remote working can be organized in an optimal way to encourage rather than discourage participation. Methods: We use an economic preference elicitation tool, a discrete choice experiment (DCE), via an online survey, to estimate public contributors' preferences for and trade‐offs between different features of remote meetings. The features were informed by previous research to include aspects of remote meetings that were relevant to public contributors and amenable to change by PPIE organizers. Results: We found that public contributors are more likely to participate in a PPIE project involving remote meetings if they are given feedback about participation; allowed to switch their camera off during meetings and step away if/when needed; were under 2.5 h long; organized during working hours, and are chaired by a moderator who can ensure that everyone contributes. Different combinations of these features can cause estimated project participation to range from 23% to 94%. When planning PPIE and engaging public contributors, we suggest that resources are focused on training moderators and ensuring public contributors receive meeting feedback. Discussion and Conclusion: Project resources should be allocated to maximize project participation. We provide recommendations for those who work in public involvement and organize meetings on how resources, such as time and financial support, should be allocated. These are based on the preferences of existing public contributors who have been involved in health and social care research. Patient or Public Contribution: We had a public contributor (Naheed Tahir) as a funded coapplicant on the UKRI ESRC application and involved members of the North West Coast Applied Research Collaboration (NWC ARC) Public Advisor Forum at every stage of the project. The survey design was informed from three focus groups held with NWC ARC public contributors. The survey was further edited and improved based on the results of six one‐to‐one meetings with public contributors.